Correlation between blood parameters in the early and later stages of pregnancy: A retrospective study - Mohd Yaacob, Noorayisahbe; Alazzam, Malik; Alziyadi, Shatha Hallal; AlGhamdi, Ahlam; Alanazi, Mansour; Alfaif, Jaber; Jumah, Jawaher Abdullah; Doheir, Mohamed A. S.; A. Hamid, Omaima; Ibrahim, Nisreen (Elsevier Ltd, 2025)
Objective: Anemia is common in pregnant women and is associated with various maternal and fetal complications. However, the effect of fluctuations in hemoglobin levels during pregnancy on birth outcomes remains unclear. Therefore, we investigated the association between maternal hemoglobin levels at different stages of pregnancy and delivery outcomes. Methods: This retrospective study included 215 women who gave birth between 2018 and 2023. Hemoglobin levels were measured at three time points during pregnancy: first trimester (approximately 12 weeks), second trimester (13–27 weeks), and third trimester (28–36 weeks). The primary outcomes were the associations between hemoglobin levels and birth weight, birth weight Z-score, placental ratio, and placental weight. Statistical analyses were conducted to control for maternal and fetal factors and to determine the correlations between hemoglobin levels and delivery outcomes.